SOIL MYCOFLORA OF BLACK PEPPER RHIZOSPHERE IN THE PHILIPPINES AND THEIR IN VITRO ANTAGONISM AGAINST Phytophthora capsici L. - Rita Noveriza; Tricita H. Quimio (Indonesian Agency for Agricultural Research and Development, 2004)
Foot rot disease of black pepper caused by Phytophthora capsici had been reported in Batangas and Laguna, Philippines. The plant was recovered following the application of crop residue (organic substrate) and intercropping with other crops. This study was aimed to isolate, identify, and determine the soil mycoflora from the rhizosphere of black pepper grown on various cropping patterns in Batangas and Laguna. Antagonistic activity of mycoflora isolates was tested against P. capsici using dual culture technique. The result showed that 149 colonies of soil mycoflora isolated were belonging to 14 genera; three of them, i.e. Penicillium, Paecilomyces and Aspergillus, were the most dominant. All of the mycoflora isolates were able to inhibit the growth of the pathogen. Eighteen of them were the most promising antagonists, based on their inhibition growth of more than 60%. It is suggested that antagonistic mechanism of Mucor isolate (1001), Trichoderma (125, 170, 171, 179, 180, 181), Gliocladium (109), Cunninghamella (165, 168), Mortierella (177), and Aspergillus (106) was space competitor (competition for nutrient) since they rapidly overgrew the pathogen. Aspergillus (67, 79, 81, 83, 108, and 202) isolates inhibited the pathogen apparently by producing antibiotic, whereas Trichoderma (125, 170, 171, 179, 180, and 181) isolates were able to penetrate the hyphae of the pathogen. The organic matter percentage in the soil was significantly correlated with the number of antagonistic mycoflora in rhizosphere (R2 = 0.1094), but the cropping pattern was negatively correlated. This study suggests that organic matter increased antagonistic mycoflora in black pepper rhizosphere, which will reduce severity of the disease.